2018
DOI: 10.1101/436642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent anti-influenza H7 human monoclonal antibody induces separation of hemagglutinin receptor binding head domains

Abstract: Seasonal influenza virus infections can cause significant morbidity and mortality, but the threat from emergence of a new pandemic influenza strain might have potentially even more devastating consequences. As such, there is intense interest in isolating and characterizing potent neutralizing antibodies that target the hemagglutinin (HA) viral surface glycoprotein. Here, we use cryo-electron microscopy to decipher the mechanism of action of a potent HA head-directed monoclonal antibody bound to an influenza H7… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 47 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…Twenty antibody classes targeting six epitopes on the prefusion closed HIV-1 Env trimer have been characterized using SPA (Table 3) and crystallographic studies (Chuang et al 2019). 'Breathing' by HIV-1 B41 SOSIP.664 trimers was found to expose the b12 epitope (Ozorowski et al 2017), and a similar motion by influenza HA protomers was also revealed by SPA (Turner et al 2019). S230 binding induces fusogenic conformational rearrangements in the SARS-CoV S glycoprotein, while the MERS-CoV S glycoprotein remains its prefusion conformation upon LCA60 binding Walls et al 2019).…”
Section: Enveloped Viruses Without Icosahedral Symmetrymentioning
confidence: 74%
“…Twenty antibody classes targeting six epitopes on the prefusion closed HIV-1 Env trimer have been characterized using SPA (Table 3) and crystallographic studies (Chuang et al 2019). 'Breathing' by HIV-1 B41 SOSIP.664 trimers was found to expose the b12 epitope (Ozorowski et al 2017), and a similar motion by influenza HA protomers was also revealed by SPA (Turner et al 2019). S230 binding induces fusogenic conformational rearrangements in the SARS-CoV S glycoprotein, while the MERS-CoV S glycoprotein remains its prefusion conformation upon LCA60 binding Walls et al 2019).…”
Section: Enveloped Viruses Without Icosahedral Symmetrymentioning
confidence: 74%
“…These findings suggest that the HA trimer is dynamic [88][89][90] and that the interface can be opened, perhaps transiently or partially, to expose conserved sites. The "breathing" of the interface of the HA head domain has also been reported [16][17][18]87]. HA0 is the HA precursor protein.…”
Section: Recent Advances In Anti-ha Antibodiesmentioning
confidence: 80%
“…This interface was previously considered to be hidden but can be exposed according to the recently proposed HA "breathing" theory [16]. Consequently, panels of broadly neutralizing antibodies targeting these epitopes were identified [16][17][18]. In the present work, we review the recent progress on these novel "universal" antibodies and discuss the potential implications of existing studies on influenza drug and vaccine development.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations